2020
DOI: 10.1101/2020.04.13.039388
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Narrowing of Dendrite Branches across Nodes follows a well-defined Scaling Law

Abstract: words)Branched networks are ubiquitous in nature, ranging in size from watercourses and trees to cellular organelles and the cytoskeleton [1][2][3][4][5] . Often, the branch diameters change systematically throughout the network, with the proximal branches frequently thicker than the distal ones. This variation is usually interpreted as an adaptation to, or consequence of, the flow of materials and/or information through the network. To describe the changes in diameter over branch points, scaling or allometric… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…An important difference between dendrite tips in class IV cells and the growth cones seen in these other cells is that the tips of class IV dendrites are much smaller. The diameter of class IV terminal dendrites is only ~200 nm (Liao et al, 2021), as small as a single filopodium, the finest feature of growth cones observed under the light microscope. Thus, tip-growth mechanisms in class IV dendrites likely differ from growth-cone-based growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An important difference between dendrite tips in class IV cells and the growth cones seen in these other cells is that the tips of class IV dendrites are much smaller. The diameter of class IV terminal dendrites is only ~200 nm (Liao et al, 2021), as small as a single filopodium, the finest feature of growth cones observed under the light microscope. Thus, tip-growth mechanisms in class IV dendrites likely differ from growth-cone-based growth.…”
Section: Discussionmentioning
confidence: 99%
“…Dendrite death occurred when the last point disappeared during a shrinkage event. Contact, defined as a tip getting closer than 0.15 m to another branch (roughly the radius of the terminal branch (Liao et al, 2021), switched a growing tip to a shrinking one with the post-contact dynamics (Table 1B).…”
Section: An Agent-based Model Incorporates Measured Tip Propertiesmentioning
confidence: 99%
“…In each step of MC optimization method, a simulated image is generated based on , where A stands for the image intensity, N stands for image photon shot noise. The MC optimization aim to find the σ and λ that minimize the square of the difference (Liao et al ., 2021): , where I sim and I exp stand for 1D intensity profiles for simulated and experimental images separately, m stands for pixel number. Six 1000-step simulations were carried out for σ and λ detection.…”
Section: Methodsmentioning
confidence: 99%
“…To see this figure in color, go online. (24). Therefore, both the narrower and wider stimuli will fall mostly within the proximal dendrites (and soma), whereas the wide stimulation will fall mostly outside the distal dendrites.…”
Section: Contact Responses Depend On the Overlap Between The Stimulus And The Dendritementioning
confidence: 99%